Milder operating parameters for one-step conversion of fructose to levulinic acid over sulfonated H-β zeolite in aqueous media - Bisen, Swapneel K.; Niphadkar, Prashant S.; Nandanwar, Sachin U.; Simakova, Irina; Bokade, Vijay V. (Environmental Progress & Sustainable Energy, 2021)
Abstract The sulfonated H-β zeolite was successfully prepared and used for the synthesis of levulinic acid (LA) from D-fructose. The catalyst was characterized by powder X-ray diffraction, Fourier transform infrared spectroscopy, scanning electron microscope, N2 physisorption, NH3-temperature programmed desorption and carbon–hydrogen–nitrogen–sulfur analysis. The total acid amount is increased with increase in sulfur loading, confirmed that the sulfonic acid group (SO3-H) is successfully grafted onto zeolite structure. The various parameters such as different amount of sulfur loading, reaction temperature, time, catalyst loading was studied for selective production of LA. The catalytic activity of sulfonated H-β (S-β) zeolite was found to be efficient for synthesis of LA from D-fructose in aqueous media. Maximum LA yield of 43.5 mol%, low HMF yield (<1%) with 98.15% fructose conversion was obtained with 3% S-β catalyst at 160°C for 7 hr. The catalyst was reusable for minimum three times by H2O2 regeneration. This study provides the new zeolitic catalyst for the efficient production of LA at shorter reaction time (7 hr) and low catalyst to substrate ratio (0.7:1).
Keywords: conversion; D-fructose; H-β; HMF; levulinic acid; sulfonated zeolite; yield